Enhanced sclerotherapy for vascular malformations: A dual-mechanism approach using in-situ forming PATDs gel - Jizhuang Ma; Wenhan Li; Yu Ding; Yongfeng Chen; Xiaoyu Huang; Tong Yu; Di Song; Haoran Niu; Bao Li; Huichao Xie; Keda Zhang; Tianzhi Yang; et al. (Materials Today Bio, 2024)
Vascular malformations are common vascular lesions in infants and seriously affect their health and quality of life. Vascular sclerotherapy is an effective treatment for vascular malformations. However, current sclerosants have difficulty achieving both high efficiency and low toxicity, and their dosing forms make it difficult to achieve long-term retention in the affected blood vessels. Therefore, exploring a safe and effective sclerosant and its delivery strategy is the key to clinical sclerotherapy. To address the above issues, this study developed sclerosants that could form an in-situ gel based on a dual mechanism of vascular injury and plasmin (PLA) inhibition. By linking the non-ionic surfactant sclerosant polyoxyethylene alkyl ether (PAs) and the PLA inhibitor tranexamic acid (TA) through an ester bond, a cationic surfactant sclerosant polyoxyethylene alkylether tranexamate derivatives (PATDs) were constructed. The cationic charge of PATDs enhanced its cytotoxicity to HUVEC-TIE2-L914F cells, and the ester bond of PATDs could be degraded by esterase in the blood, reducing its systemic toxicity. The degradation product TA inhibited the activation of the PLA-matrix metalloproteinase (MMPs) system induced by vascular injury, thereby promoting the deposition of collagen and the proliferation and differentiation of fibroblasts to promote vascular fibrosis. In addition, an injectable solution (PATDs/GA) was prepared by mixing PATDs with glycerol formaldehyde (GA), and PATDs/GA could form a low-molecular-weight gel automatically in an aqueous solution, which was beneficial to increase its retention in the affected blood vessels and reduce the risk of drug entering non-targeted sites. At the same time, this gel automatically dissolved, reducing the risk of immune rejection caused by long-term retention. This study provided a new and precise approach for the treatment of vascular sclerosis with high efficiency and low toxicity.